2021
DOI: 10.1111/tpj.15308
|View full text |Cite
|
Sign up to set email alerts
|

Polygalacturonase45 cleaves pectin and links cell proliferation and morphogenesis to leaf curvature in Arabidopsis thaliana

Abstract: Regulating plant architecture is a major goal in current breeding programs. Previous studies have increased our understanding of the genetic regulation of plant architecture, but it is also essential to understand how organ morphology is controlled at the cellular level. In the cell wall, pectin modification and degradation are required for organ morphogenesis, and these processes involve a series of pectin-modifying enzymes. Polygalacturonases (PGs) are a major group of pectin-hydrolyzing enzymes that cleave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 62 publications
(95 reference statements)
1
32
0
Order By: Relevance
“…Previous studies have demonstrated that a PG protein in Brassica campestris, BcMF23, was a secreted protein and exhibited extracellular localization by subcellular localization of onion epidermis transient expression [50]. In transgenic Arabidopsis, ATPGX3 and AtPG45 were located in the cell wall [51,52]. The present transient expression result in the onion epidermis confirmed that SlPG49 was a secreted protein and may play a great role in the cell wall or extracellular matrix (Figure 3), similar to PGs in A. thaliana.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies have demonstrated that a PG protein in Brassica campestris, BcMF23, was a secreted protein and exhibited extracellular localization by subcellular localization of onion epidermis transient expression [50]. In transgenic Arabidopsis, ATPGX3 and AtPG45 were located in the cell wall [51,52]. The present transient expression result in the onion epidermis confirmed that SlPG49 was a secreted protein and may play a great role in the cell wall or extracellular matrix (Figure 3), similar to PGs in A. thaliana.…”
Section: Discussionsupporting
confidence: 80%
“…The present transient expression result in the onion epidermis confirmed that SlPG49 was a secreted protein and may play a great role in the cell wall or extracellular matrix (Figure 3), similar to PGs in A. thaliana. To date, only nine PG genes have been identified in A. thaliana, with five that have been proven to show PG activity in vitro [51,[53][54][55]. However, there is no report of in vitro activity of PGs in tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…Pectinaseterase hydrolyzes the methyl ester in the pectin and promotes the production of pectic acid, which may be the substrate of PG. PG hydrolyzes the pectin substance in the intercellular layer during cell separation [ 13 , 14 ]. The effects of specific functional genes on organ shedding may be common to different species, but the signals that trigger their expression may be different [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several Arabidopsis PG genes from the large polygalacturonase gene family have been recently reported to function in hypocotyl elongation, leaf and flower morphogenesis, pollen and pollen tube development, and stem growth ( Ogawa et al, 2009 ; Xiao et al, 2014 , 2017 ; Rui et al, 2017 ; Hocq et al, 2020 ; Yang et al, 2021 ). Importantly, we previously reported that the polygalacturonase gene, PGX2 , affects primary root length ( Xiao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ARABIDOPSIS DEHISCENCE ZONE POLYGALACTURONASE1 ( ADPG1 ) and ADPG2 regulate floral organ abscission and anther dehiscence ( Ogawa et al, 2009 ). Recently, another polygalacturonase, PG45 functions in leaf curvature ( Yang et al, 2021 ). These characterized polygalacturonase genes are from different clades of phylogenetic tree ( Xiao et al, 2014 ) and play important functions in multiple different organs during plant growth and development.…”
Section: Introductionmentioning
confidence: 99%